(untitled) (International Journal of Food and Nutritional Sciences, 2022)
With a globalization of world economy and the growing level of competition the increase in knowledge and awareness because of social media and issues like women empowerment and feminism the involvement of women has increased in each and every aspects whether you say it home, small scale business or in big multinational organizations they have proven their skills and caliber everywhere but in lieu of balancing everything they usually ignore their own health and mental wellbeing which usually has a long term impact on not only them but also the peoples around them this research paper brings into light various problems that a women employee face with the help of personal interviews taken by various women employees working on different academic organizations. A descriptive study was conducted of 150 women about the personal opinion of about the problem faced by them in the working environment as well as at home leading to work life imbalance.